Water Quality of Melamchi River of Sindhupalchok District, Central Nepal - Mishra, Abhr R; Gupta, Ranjana (Journal of Natural History Museum, 2018)
The present study was carried out to estimate the physico-chemical characteristic of Melamchi River from January 2011 to December 2013 with a view to assess the nature and degree of pollution. Melamchi River is a snowmelt and rain fed river. River water is mainly used for drinking and irrigation. Water samples were collected on monthly basis from five sites of river. Parameters analyzed include temperature, electrical conductivity, turbidity, pH, hardness, alkalinity, dissolved oxygen, calcium, magnesium, chloride, phosphate, and nitrate. The study revealed seasonal fluctuations of the factors. River water was well oxygenated and alkaline in nature. High level for turbidity (43.25/ NTU) was observed during monsoon, which exceeded compliance levels of WHO (2011) tolerance limits (5/ NTU) for domestic use. Water contained more TDS and EC indicating the impact of agriculture and deforestation near the river area. The analyzed physico-chemical parameters were found within the permissible limit of WHO, except turbidity. Measures should be taken to regulate agricultural and deforestation activities upriver to avoid advert conditions. J. Nat. Hist. Mus. Vol. 29, 2015, Page: 9-18